Plasma from patients undergoing allogeneic hematopoietic stem cell transplantation promotes NETOSIS in vitro and correlates with inflammatory parameters and clinical severity - López-Andrade, Bernardo; Cunill, Vanesa; Andreu, Valero; Bento, Leyre; Segura-Guerrero, Marina; Moñino, Andrea; Iglesias, Julio; Julià, Maria Rosa; Durán, Maria Antonia; Ballester, Maria Carmen; Muncunill, Josep; Sampol, Antonia (Frontiers in Immunology, 2024)
NETosis, the mechanism by which neutrophils release extracellular traps (NETs), is closely related to inflammation. During the allogeneic hematopoietic stem cell transplantation (allo-HSCT), different stimuli can induce NETs formation. Inflammation and endothelial injury have been associated with acute graft-versus-host disease (aGVHD) and complications after allo-HSCT. We focus on the study of NETosis and its relation with cytokines, hematological and biochemical parameters and clinical outcomes before, during and after allo-HSCT. We evaluate the capacity of plasma samples from allo-HSCT patients to induce NETosis, in a cell culture model. Plasma samples from patients undergoing allo-HSCT had a stronger higher NETs induction capacity (NETsIC) than plasma from healthy donors throughout the transplantation process. An optimal cut-off value by ROC analysis was established to discriminate between patients whose plasma triggered NETosis (NETs+IC group) and those who did not (NETs-IC group). Prior to conditioning treatment, the capacity of plasma samples to trigger NETosis was significantly correlated with the Endothelial Activation and Stress Index (EASIX) score. At day 5 after transplant, patients with a positive NETsIC had higher interleukin (IL)-6 and C-reactive protein (CRP) levels and also a higher Modified EASIX score (M-EASIX) than patients with a negative NETsIC. EASIX and M-EASIX scores seek to determine inflammation and endothelium damage, therefore it could indicate a heightened immune response and inflammation in the group of patients with a positive NETsIC. Cytokine levels, specifically IL-8 and IL-6, significantly increased after allo-HSCT with peak levels reached on day 10 after graft infusion. Only, IL-10 and IL-6 levels were significantly higher in patients with a positive NETsIC. In our small cohort, higher IL-6 and IL-8 levels were related to early severe complications (before day 15 after transplant). Although early complications were not related to NETosis by itself, NETosis could predict overall non-specific but clinically significant complications during the full patient admission. In summary, NETosis can be directly induced by plasma from allo-HSCT patients and NETsIC was associated with clinical indicators of disease severity, cytokines levels and inflammatory markers.